Wheat varietal response to organic fertilization under Casuarina (Casuarina junghuhniana Miq.) based agrisilviculture system in trans-Gangetic Plains - Shivam; Sandeep, A; Chhavi, S; Visha, J; Anjali, T; Hemant, K; Sanjay, K V; Ratan, K A; Shashi, B S P; Vikas, K (Plant Science Today, 2026)
The study examined wheat varieties under a Casuarina (Casuarina junghuhniana Miq.) - based agrisilviculture system (CASs) with organic fertilizer at the Department of Forestry, CCS Haryana Agricultural University, Hisar, during the rabi season of 2022-23. Casuarina trees (spaced at 5 × 3 m) showed growth increments of 0.4 m in height, 1.85 cm in girth and 0.2 m in crown spread during the study. Organic fertilizer treatments significantly enhanced soil organic carbon, available nitrogen (N), phosphorus (P), potassium (K) and Diethylenetriaminepentaacetic acid (DTPA)-extractable micronutrients, including zinc (Zn), iron (Fe), copper (Cu) and manganese (Mn), compared with the control (open field). However, lower soil moisture and reduced light availability (by 54.5–59.3 %) were observed under the agroforestry system. Air temperature was slightly lower and relative humidity was higher under the Casuarina canopy. Growth, physiological and yield parameters of wheat were generally superior in the sole crop compared to the agroforestry system, except for relative stress injury (RSI) (%), N balance index (NBI), chlorophyll index (CHI) and canopy temperature depression (CTD). Among the varieties tested, WH 1270 recorded the highest test weight, dry matter accumulation, grain yield (GY) and harvest index (HI) under Casuarina. WH 1142 showed the greatest yield reduction (35.31 %) under tree shade, indicating high shade sensitivity. Wheat responded best to T1 (150 kg ha-1 Recommended Dose of Nitrogen (RDN) via inorganic fertilizers), with higher NBI, CHI and yield parameters, highlighting its effectiveness even under CASs. The result indicates nutrient content was consistently higher under the agroforestry system than under sole cropping, reinforcing its relevance for developing climate-resilient production systems that enhance soil conservation, diversify income and lessen environmental pressures.